2013
DOI: 10.2169/internalmedicine.52.9577
|View full text |Cite
|
Sign up to set email alerts
|

Demyelinating Neuropathy and Autoimmune Hemolytic Anemia in a Patient with Pancreatic Cancer

Abstract: We herein report the case of a patient with pancreatic cancer who manifested features of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and autoimmune hemolytic anemia (AIHA). A 78-year-old Japanese man presented with AIHA and was treated with steroids and splenectomy. Although the AIHA improved following splenectomy, the patient suffered from sensorimotor neuropathy soon after undergoing surgery. The electrophysiological features indicated demyelinating neuropathy. The neuropathy was refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…Other solid tumours associated with AIHA were essentially lung, kidneys and colorectal cancers and Kaposi syndrome 3. In addition to previously cited case, AIHA related to pancreatic cancer was reported, to our knowledge, in only another case of a 71-year-old man presenting pancreatic adenocarcinoma with demyelinating neuropathy and AIHA, confirming the rarity of such paraneoplastic syndrome 11…”
Section: Discussionsupporting
confidence: 70%
“…Other solid tumours associated with AIHA were essentially lung, kidneys and colorectal cancers and Kaposi syndrome 3. In addition to previously cited case, AIHA related to pancreatic cancer was reported, to our knowledge, in only another case of a 71-year-old man presenting pancreatic adenocarcinoma with demyelinating neuropathy and AIHA, confirming the rarity of such paraneoplastic syndrome 11…”
Section: Discussionsupporting
confidence: 70%
“…In as much as 7% of patients with various solid tumors including pancreatic cancer, disseminated intravascular coagulation is observed [21] which can lead to hemolytic anemia potentially reducing hemoglobin levels. Hemolytic anema cases in pancreatic cancers have been reported [22]. On the other hand Claspin had higher levels in HG compared to controls and it was also high in LG and IPMNC.…”
Section: Discussionmentioning
confidence: 92%
“…Management of pain as a result of paraneoplastic neuropathy does not differ from the published guidelines on the management of neuropathic pain [ 50 ]. However, it is commonly reported that treatment for the underlying malignancy (including tumor resection and/or chemotherapy) can improve the symptoms [ 3 , 11 , 28 , 30 , 37 ].…”
Section: Resultsmentioning
confidence: 99%